Cellular Evidence and Source of Exosomes in the Biliary System of the Chinese Soft-Shelled Turtle, Pelodiscus sinensis - Zhu, Xudong; Wang, Siyi; Tarique, Imran; An, Tianci; Yang, Huan; Bai, Xuebing; Wang, XiaoFei; Chen, Qiusheng; Yang, Ping (Frontiers in Physiology, 2019)
Exosomes are 40–150nm extracellular vesicles with a size of 40–150 nm that are released from a multitude of cell types, and are present in biological fluids, which that are particularly rich in membrane proteins. These vesicles are present in the bile, where they function as a are special regulator of the digestive system; however,, but their source and characteristic in normal gallbladders have never been discovered. Bile, liver, and gallbladder were obtained from healthy turtles after starvation treatment from healthy turtles. Biliary exosomes were extracted through Total Exosomes Isolation Kit. Theand their morphology, particle sizes, and specific proteins were characterized by transmission electron microscope (TEM), nanoparticle tracking analysis (NTA), SDS-PAGE staining, and Western blotting. Furthermore, immunohistochemistry and TEM was were used to investigate the distribution of exosomes in both liver and gallbladder. TEM exhibited that Bbiliary exosomes were had a round or oval shape with obvious apparent bilayer membranes. Biliary exosomes were uniform in size, with a range from 40 to 180 nm in diameter. Immunohistochemistry showed that the CD63 exosome marker was positive and primarily distributed in the hepatocyte junction, while the free surface of gallbladder was tested negative. In addition, TEM results showed that exosomes were present in bile but, while absent on the apical free surface of gallbladder. This study provides direct evidences that biliary exosomes secreted by hepatocytes into bile canaliculus and flow with bile into the gallbladder. The source and the isolated protocol of biliary exosomes may provide technical support and a theoretical basis for the exploration ofing the potential antiviral or anti-inflammatory properties of biliary exosomes.